RT-nested PCR for the detection of enterovirus in biological samples from patients with suspected enteroviral infections - Poggio Palacios, Gustavo (2000)
Fil: Poggio Palacios, Gustavo. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología. Servicio de Neurovirosis; Argentina.